Pencirian Mutu Kimiawi dan Mikrobiologis Produk Bandrek Instan dan Sirup Buah Pala (Myristica fragrans) - Didah Nur Faridah; Sedarnawati Yasni; Antin Suswantinah; Ghesi Wuri Aryani (Jurnal Ilmu Pertanian Indonesia, 2013)
The aim of this study was to find chemical and microbiological characteristics of instant bandrek and nutmeg syrup from Sinarsari and Dramaga villages, Dramaga District, Bogor Regency. The analysis resulted that both products still fulfilled the quality standard of microbiological set by the Indonesian National Standard. The antioxidant capacity of instant bandrek and nutmeg syrup consecutively was equivalent with 256.12 mg AEAC per serving size and 775.62 mg AEAC per serving size, respectively. The toal phenolic of the instant bandrek drink and nutmeg syrup consecutively was equivalent with 89.81 mg GAE/L and 140.68 mg GAE/L, respectively. It can be concluded that the food processing did not remove the bioactive compounds that could function as antioxidant.